Efektivitas pelatihan partisipatif dalam peningkatan kompetensi mekanik pompa air: Studi Percontohan di Kabupaten Bandung - Adhi, Pribadi Mumpuni; Belyamin, Belyamin; Susanto, Iwan; Rahman, Haolia; Kamal, Dianta Mustofa; Pramono, Agus Edy; Nufus, Tatun Hayatun; Sukusno, Paulus; Nidhar, Ainun; Ramadhan, Mochammad Tendi Noer (Politeknik Kesehatan Kemenkes Aceh, 2025)
Farmers’ skills in maintaining water pumps remain limited, although these skills are essential for sustaining agricultural production. This study is presented as a pilot study aimed at assessing the effectiveness of participatory training in improving the knowledge, skills, and attitudes of water pump mechanics. The study involved nine mechanics under the guidance of UPTD ALSINTAN Dinas Pertanian Kabupaten Bandung, each representing one of nine affiliated areas. Evaluation was conducted using pre-test and post-test instruments with 20 items on a five-point Likert scale, analyzed descriptively without inferential statistics. The initial findings indicated an increase in the overall mean score from 3.55 to 4.78, with the largest improvements observed in skills (+46.27%) and knowledge (+39,83%). These results suggest improvements in competence, although they remain exploratory. The main limitations of this study are the small sample size and reliance on self-reported measures. Further studies with larger samples and stronger designs are recommended.